Characteristics of traditionally processed shea kernels and butter. (2nd May 2013) - Honfo, Fernande G.; Linnemann, Anita R.; Akissoe, Noel; Soumanou, Mohamed M.; van Boekel, Martinus A. J. S.
Summary: The traditional production of shea butter requires a heat treatment of the nuts. This study compared the end products derived by two commonly used heat treatments, namely smoking and boiling followed by sun‐drying. Neither treatment influenced the moisture content of the kernels (8–10%), but the boiling treatment resulted in more free fatty acids (FFA) (6%) and a higher fat content (41%) of kernels. A sensory panel preferred shea butter from boiled kernels because of its soft texture and intense smell. This butter also had the highest values for moisture content (2%), unsaponifiable matter (7%), tocopherol compounds (125 mg g −1 ), peroxide value (8 meq O2  kg −1 ), iodine value (53 mg I2  100 g −1 ) and FFA (2%). Minor variations were noticed in the fatty acid profile. Aside from the use of butter from both boiled and smoked kernels in cosmetics, the butter from smoked kernels will be more suitable for food purposes.